Prevalence of anhedonia in women with deep endometriosis - Aida Mallorquí; Alessandra Fortuna; Emma Segura; Gemma Cardona; Marta Espinosa; Lara Quintas-Marquès; Meritxell Gracia; Elena Angulo-Antúnez; Francisco Carmona; María-Angeles Martínez-Zamora (Scientific Reports, 2025)
Abstract Anhedonia, characterized by diminished motivation and pleasure sensitivity, is increasingly recognized as prevalent among patients with chronic pain. Deep Endometriosis (DE), the most severe endophenotype of the disease, is commonly presented with chronic pelvic pain. This cross-sectional study reports, for the first time, the prevalence of anhedonia in a sample comprised by 212 premenopausal women with suspected DE referred to a tertiary hospital. Our findings show that 27,8% [95% CI 22.1, 26.5] of DE patients experience abnormal hedonic tone. Severity of DE pain-related symptoms significantly correlated with anhedonia, consistent with previous findings. Chronic pelvic pain emerged as a significant predictor of anhedonia (OR 1.5, 95% CI 1.0–1.22, p < 0.05) with the odds increasing to 2.28 [95% CI 1.12, 4.23] when pain was severe. The most affected areas in DE patients were interests, social interaction and food pleasure. The present results are representative of DE patients under multimodal treatment, limiting generalizability. Overall, our study highlights the impact of chronic pain on hedonic functioning in DE. Therapeutic approaches targeting hedonic capacity in DE patients are crucial for restoring health and well-being.